Responses of soil microbial communities and enzyme activities under nitrogen addition in fluvo-aquic and black soil of North China - Ullah, Sami; Raza, Muhammad Mohsin; Abbas, Tanveer; Guan, Xian; Zhou, Wei; He, Ping (Frontiers in Microbiology, 2023)
This research investigates the impact of long-term N addition on fluvo-aquic and black soils in north China, with a focus on soil microbial communities and enzyme activities. In each site, there were three N fertilization treatments, i.e., control, moderate-N, and high-N. Phospholipid Fatty Acid Analysis was employed to analyze the microbial community composition, and enzyme activities related to carbon (C), nitrogen (N), and phosphorus (P) cycling were assessed. The results showed that increasing N fertilization levels led to higher soil organic carbon (SOC) and total N (TN) concentrations, indicating enhanced nutrient availability. N fertilization reduced soil pH across both soils, with a more pronounced acidification effect observed in the black soil. Across both soils, N addition increased maize yield, but the higher crop yield was attained in moderate-N rate compared with high-N rate. Microbial community composition analysis revealed that N fertilization induced shifts in the relative abundances of specific microbial groups. The black soil exhibited pronounced shifts in the microbial groups compared to the fluvo-aquic soil, i.e., decreased fungal abundance and fungi:bacteria ratio in response to N input. In addition, the application of N fertilizer led to an elevated ratio of gram-positive to gram-negative (GP:GN) bacteria, but this effect was observed only in black soil. N fertilization had an impact on the enzyme activities related to C, N, and P cycling in both soil types, but black soil showed more pronounced changes in enzyme activities. Permutational multivariate analysis of variance indicated that soil types rather than N fertilization mediated the response of the soil microbial community and enzyme activities. Partial least square path modeling demonstrated that soil pH was the only key driver impacting soil microbial groups and enzyme activities in both soils. In conclusion, our findings highlighted that N fertilization exerted more pronounced impacts on soil biochemical properties, microbial community composition, and enzyme activities in black soil furthermore, moderate N rate resulted in higher crop productivity over high N rate.